The role of dynapenia and abdominal obesity in determining fall risk in the elderly (Annals of Medical Research, 2022)
Aim: Dynapenia (D) and abdominal obesity (AO) are associated with many adverse health outcomes in the elderly. In our study, we aimed to evaluate the role of dynapenia and abdominal obesity in determining the risk of falling in the elderly.Materials and Methods: A total of 400 (71.6±5.9) elderly, 228 of whom were women, were included in the study. All participants were evaluated with anthropometric measurements as well as hand grip strength, gait speed and Tinetti Balance and Gait Assesment (TBGA). AO was defined by waist circumference (WC) (WC≥102 cm in men and WC≥88 cm in women). Hand grip strength (HGS) was measured by hand dynamometry. Those with HGS